Effect of Memantine on Cognitive Performance in Patients Under Electroconvulsive Therapy: A Double-Blind Randomized Clinical Trial. Issue 6 (November 2015) - Alizadeh, Narges Shams; Maroufi, Azad; Jamshidi, Mehnoosh; Hassanzadeh, Kambiz; Gharibi, Fardin; Ghaderi, Ebrahim
Abstract : Objectives: Various strategies such as adding cholinesterase inhibitors are used to reduce cognitive impairments during electroconvulsive therapy. In this study, we aimed to assess the effectiveness and safety of memantine as an N -methyl-D-aspartate receptor antagonist in the prevention of cognitive deficits due to ECT. Methods: Thirty-eight adult patients with various mental disorders were randomized to memantine (10 mg/day initially and 20 mg/day at the end of the first week) or placebo during the ECT period. Mini Mental Status Examination, Digit Span Subtest, and backward memory span of Wechsler Adult Intelligence Scale were used to assess the cognitive functions 24 hours before and after ECT. Subjective ratings of side effects were obtained in the first, second, and fourth week of the treatment. Results: The mean Mini Mental Status Examination score relatively increased in the intervention group showing a significant improvement with memantine ( P < 0.001). The direct digit span had decreased in the control group, whereas no significant change was observed in the intervention group ( P < 0.001). Backward memory span test showed a decrease in the control group after the ECT sessions, whereas a relative increase was observed in the intervention group ( P = 0.001). The most frequently reported side effects in the intervention group did not differ significantly from the control group. Conclusions: This initial study showed that cognitive performance was enhanced in patients receiving memantine during ECT, indicating the possible role of the glutamatergic system in creating ECT-induced deficits. Larger long-term studies are necessary for understanding the role of the glutamatergic system in these disorders.